(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The problem of technological knowledge formalization is being considered. Discussed features of systems in the scope of ontological engineering of processes, applied to solving the problems of the structural representation of technologies associated with the organization of their analysis. Proposed a model of the concept of technological action, which identifies technological actions as holistic conceptual formations. Constructed the model of formalized description of technologies, which provides unambiguous transition from verbal descriptions of technologies to their ontological representations. Described algorithms for constructing a formalized description of technologies, which implement the logical procedures for automated and automatic construction of ontological representations of technologies. Concluded in the development of a new method of formalized description of technologies, the fundamental principles of which constitute the distinctive features of the proposed models and constructed algorithms.